2017
DOI: 10.5376/ijms.2017.07.0022
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Metal Pollution in Sediments along Sinop peninsula of the Black Sea

Abstract: The spatial distribution pattern and transportation of heavy metals in sediments (up to 10 cm) were studied along Sinop peninsula of the southern Black Sea. The influences of anthropogenic metals pollution in surface sediments of Sinop Peninsula in the Black Sea were assayed by using I geo. Metal contents were significantly correlated each other. Heavy metal concentrations showed a significant relationship with Fe content, while most heavy metals were not enriched. The levels of most metals at all stations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
6
1
Order By: Relevance
“…Considering the inter-annual variations of As and Hg concentrations in the study area (Table 1), the differences observed in our study were within this variation range (Huo, 2011). Moreover, the concentrations in our study were not higher than other areas in China (such as the Yellow Sea) or in other parts of the world, such as the Black Sea (Guo, 2011;Lan et al, 2014;Bat et al, 2017). The As concentrations in our study approached the standard of Grade I (<20 mg/g), and the Hg concentrations approached Grade II (<0.05 mg/g) according to the marine sediment quality guidelines established by the P. R. China (GB 18668-2002).…”
Section: Heavy Metalscontrasting
confidence: 54%
“…Considering the inter-annual variations of As and Hg concentrations in the study area (Table 1), the differences observed in our study were within this variation range (Huo, 2011). Moreover, the concentrations in our study were not higher than other areas in China (such as the Yellow Sea) or in other parts of the world, such as the Black Sea (Guo, 2011;Lan et al, 2014;Bat et al, 2017). The As concentrations in our study approached the standard of Grade I (<20 mg/g), and the Hg concentrations approached Grade II (<0.05 mg/g) according to the marine sediment quality guidelines established by the P. R. China (GB 18668-2002).…”
Section: Heavy Metalscontrasting
confidence: 54%
“…Holothuroids are deposit-feeders and live in close association with sediment, and feeds mainly detrital particles and associated microorganisms (WoRMS Editorial Board, 2018). Many studies 2017; indicated that heavy metals including Hg tend to accumulate in sediment. It is surprising that H. arenicola, H. pardalis, H. verrucosa and H. atra, which are benthic species and are associated with sediment, did not show the high levels of Hg.…”
Section: Resultsmentioning
confidence: 99%
“…Another macroalgae species, Padina sp., was used to synthesise AgNPs with antimicrobial properties. 87 The AgNPs with ∼ 25 nm – 60 nm in size were reported to be highly potent against Staphylococcus aureus and Pseudomonas aeruginosa .…”
Section: A Current Trend In Agnps Synthesis (Biological Method)mentioning
confidence: 99%